A comprehensive survey on quality of service implementations in cloud computing - Firdhous, Mohamed; Hassan, Suhaidi; Ghazali, Osman (2013)
Quality of service plays is an important factor in distributed computing.Cloud computing has been the paradigm in distributed computing.Under cloud computing, computing resources are hosted in the internet and delivered to customers as services.Prior to the commencement of services, the customers and cloud providers negotiate and enter into an agreement named service level agreement.The services level agreements clarify the roles, set charges and expectations and provide mechanisms for resolving service problems within a specified and agreed upon time period. Service level agreements also cover performance, reliability conditions in terms of quality of service guarantees. In this paper, the authors present a comprehensive survey on quality of service implementations in cloud computing with respect to their implementation details, strengths and weaknesses.